Interim Alternative Educational Settings for Students with Disabilities Involved in Disciplinary Actions. Policy Forum Report - National Association of State Directors of Special Education, Alexandria, VA.; National Association of State Directors of Special Education, Alexandria, VA. ([S.l.] : Distributed by ERIC Clearinghouse, 1998)
This document is the report of a policy forum on interim alternative educational settings for students with disabilities involved in disciplinary actions. The report summarizes outcomes of discussions on the following topics: (1) purpose and goals of the interim alternative educational setting; (2) components of interim alternative educational settings required by the 1997 amendments of the Individuals with Disabilities Education Act (Sec. 615 (k)); (3) components/features of effective alternative programs; (4) interagency collaboration; (5) family participation; (6) policy issues/concerns and how to address them; and (7) funding considerations and possible solutions. Appendices, which comprise half of the document, include: the policy forum agenda; a list of strategies used by effective classroom managers to create classroom climates that prevent discipline problems; a list of the 10 most common discipline strategies; models and techniques that focus on correction of misbehavior; and papers on the effect of suspension-expulsion on students with disabilities, disciplining students with disabilities, and school psychology and behavioral interventions. (CR)
Availability: Project FORUM, National Association of State Directors of Special Education, 1800 Diagonal Road, Suite 320, Alexandria, VA 22314.
Sponsoring Agency: Special Education Programs (ED/OSERS), Washington, DC.
Contract Number: HS92015001.
ERIC Note: Prepared by Project FORUM (Chandler, AZ, October 18-20, 1997).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Agency Cooperation; Behavior Problems; Classroom Techniques; Disabilities; Discipline; Discipline Policy; Educational Legislation; Elementary Secondary Education; Expulsion; Family Involvement; Nontraditional Education; Prevention; Program Costs; Program Effectiveness; Program Implementation; Special Schools; Student Placement; Suspension; Interim Alternative Educational Settings; Individuals with Disabilities Educ Act Amend 1997; Reports, Descriptive